Legal Protection of Halal Tourism Stakeholders in The Globalization Era - Rustamaji, Muhammad; Gunawan, Matthew Marcellinno (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Legal protection is the most important thing in the business world on globalisation era, including in the tourismsector. It is even very urgent if the business field is something that is considered less in accordance with the religiousprovisions adopted by the surrounding community, in this case the Madurese community. An island that has manynatural resources to be used as a tourist attraction. The purpose of this study was to determine the concept or modelof legal protection for tourism stakeholders in Madura. This research is a field research with a descriptive-qualitativeapproach located on the island of Madura which consists of 4 districts, Bangkalan, Sampang, Pamekasan andSumenep. Data collection was done by means of snowball sampling. After the data is collected then it is processedand analyzed by qualitative analysis with inductive logic. The results of this study indicate that the legal protectionof stakeholders in Madura refers to village regulations and cooperation agreements between parties in the tourismbusiness, for example between village-owned enterprises and tourism awareness groups (pokdarwis) as tourism objectmanagers, and between tourism object managers and third party.Keywords: Legal protection; halal tourism; globalisation